MANAJEMEN KINERJA APARATUR SIPIL NEGARA (ASN) BERBASIS BEKERJA DARI RUMAH (WORK FROM HOME) - tjahyo tjahyo rawinarno; Haryo Setyoko; Agus Widiarto; Suhud Alynudin (NIAGARA Scientific Journal, 2023)
Nearly 50% of civil servants did not complete their work in the third month of the pandemic because the Work From Home system was implemented in Indonesian government agencies. Facing the Covid-19 crisis, the government needs to pay more attention to apparatus performance management. One of the models used is integrated performance management according to Zainal (2014) which in outline consists of planning, training and evaluation. The research method used is literature study, such as legal institution documents. Referring to Government Regulation Number 30 of 2019 concerning the Assessment of Civil Servant Performance Management, it already contains part of the performance management model, namely the Civil Servants Performance Targets.